Exceptional Sets for Sums of Prime Cubes in Short Interval - Gongrui Chen (Journal of Mathematics)
Let EN,X denote the number of even integers n, with N−X≤n≤N, such that n cannot be written as n=p13+⋯+p83. We prove that if X>N1/36+ɛ, then EN,X=oX.